Interaction study of arsenic (III and V) ions with metallothionein gene (MT2A) fragment - Nejdl, Lukas; Skalickova, Sylvie; Kudr, Jiri; Ruttkay-Nedecky, Branislav; Dostalova, Simona; Kremplova, Monika; Kensova, Renata; Moulick, Amitava; Konecna, Marie; Adam, Vojtech; Kizek, Rene (International journal of biological macromolecules, 2015)
Arsenic compounds belong to the most controversial agents concerning human health. Arsenic (As) is considered as a top environmental element influencing human health due to its adverse effects including cancer, diabetes, cardiovascular disease, and reproductive or developmental problems. Despite the proven mutagenic, teratogenic and carcinogenic effects, the arsenic compounds are used for centuries to treat infectious diseases. In our work, we focused on studying of interactions of As(III) and/or As(V) with DNA. Interactions between arsenic ions and DNA were monitored by UV/vis spectrophotometry by measuring absorption and fluorescence spectra, atomic absorption spectrometry, electrochemical measurements (square wave voltammetry) and agarose gel electrophoresis. Using these methods, we observed a stable structure of DNA with As(III) within the concentration range 0.4-6.25 μg mL(-1). Higher As(III) concentration caused degradation of DNA. However, similar effects were not observed for As(V).
Keywords: metalothionein; Communicable Diseases; Spectrophotometry, Atomic; Metallothionein; DNA Interaction; DNA Fragmentation; fragmentace DNA; DNA; lidé; arsen; Antineoplastic Agents; protinádorové látky; Anticancer drug; infekční nemoci; spektrofotometrie atomová; Electrochemistry; Spectrometry; Arsenic; ionty; Ions; Humans